Surgical experiences in pediatric pilomatricoma: punch incision and elliptical excision - Hoon Choi; Dong Hyun Shim; Chan Ho Na; Bong Seok Shin; Min Sung Kim (Taylor & Francis Group, 2023)
Background As pilomatricoma is a common adnexal skin tumor often occurring in exposed areas, dermatologists focus on minimizing postsurgical scarring. Methods This retrospective study included patients aged < 19 years who underwent surgical treatment for pilomatricoma at a single university hospital from 2015 to 2021. Patient demographics, tumor characteristics, and surgical outcomes were analyzed according to the surgical methods including punch incision and elliptical excision. Results Overall, 75 patients and 79 lesions were included in the study. The mean age of the patients was 8.4 years, and 48 patients (64.0%) were females. The face was the most common site of pilomatricoma (51.9%), and within the face, the cheeks were the most common sites. No recurrence was observed in the elliptical excision group, while one case of recurrence (4.5%) was observed in the punch incision group. The mean length of the wound was 2.00 cm in the elliptical excision group, which was longer than that in the punch incision group (0.49 cm; p < .001). Conclusions Considering that surgery is the gold standard treatment for pilomatricoma, punch incision may be useful as an alternative surgical option for pilomatricoma in children.